Clinicohistopathological correlation of leprosy (Journal of Pathology of Nepal, 2017)
BACKGROUND: Leprosy is a chronic infectious granulomatous disease caused by Mycobacterium leprae. It is a spectral disease which is classified into five groups according to Ridley and Jopling based on clinical, histological, microbiological and immunological criteria. Adequate clinical information combined with bacilloscopy and histopathology is helpful not only in classification of different types of leprosy but also useful for management of the cases.METHOD: 50 cases of leprosy were examined and clinical data was recorded. Slit skin smears were stained with Ziehl Neelsen stain. Skin biopsy was stained with Hematoxylin-Eosin stain and Fite Farraco stain was performed to demonstrate acid fast bacilli. All patients were classified according to Ridley & Jopling classification. Clinico-histopathological correlation was done. Statistical analysis was done using SPSS (Statistical Package for the Social Sciences) 16.0.RESULTS: Most common histological type of leprosy was tuberculoid leprosy seen in 19(38%) cases followed by indeterminate leprosy. Overall clinico-histopathological correlation was seen in 39.58%. The correlation was highest in indeterminate and histoid leprosy (100%) followed by lepromatous leprosy (66.66 %%) and tuberculoid leprosy (50%). Slit skin smear showed bacilli in 12 out of 48 cases (25%) while biopsy showed bacilli in 16 out of 48 cases (33.3%).CONCLUSION: In the present study, clinical diagnosis did not correlate with histopathological diagnosis significantly (p value=0.04159). The study emphasizes the role of histopathological and bacilloscopic examination to aid the clinical diagnosis for accurate typing of leprosy cases then better management of the patient.